Sosialisasi Cyberbullying dan Pergaulan Bebas di SDN Makasar 07 Pagi - Muhammad Saiful Zacky; Kirania Tama Putri Hidayat; Nafira Utami Putri; Reyza Ahmad Abdul Jabbar; Hanif Azzulfikri; Stefanus Delson; Muhamadau Utama; Aldi Aditya; Luthfi Hardiyanto (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Cyberbullying and promiscuity are common problems nowadays due to uncontrolled technology use and lack of parental supervision. Cyberbullying and promiscuity are actions that violate societal norms and values. This activity highlights various forms of Cyberbullying and promiscuity such as spreading fake news, insulting on social media, juvenile delinquency, drugs, smoking, and alcohol. This socialization activity aims to provide an understanding of the dangers of Cyberbullying and promiscuity and provide ways to prevent them. The methods used in the socialization are in the form of direct delivery of material, dicusstion, and providing examples of cases in everyday life.The results of this socialization show that children understand Cyberbullying and promiscuity and the negative impact they have on children, and children also become more aware of the importace of being careful in using social media and socializing. It is hoped that children can grow with good, positive behavior, and avoid negative influences from the environment and digital media.